2013
DOI: 10.1063/1.4803535
|View full text |Cite
|
Sign up to set email alerts
|

Narrow plasmon resonances in diffractive arrays of gold nanoparticles in asymmetric environment: Experimental studies

Abstract: We examine experimentally the excitation of plasmon resonances in ordered two-dimensional diffractive arrays of gold nanoparticles placed in asymmetric refractive index environment. The excitation of the plasmon modes with narrow spectral profile in asymmetric environment was experimentally verified. The ability to tune the wavelength of these resonances in the near infrared range by varying the structural parameters of the periodic arrays in combination with size and geometry of the constituent nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 23 publications
0
46
2
Order By: Relevance
“…Schatz et al [11,12] have first suggested that these narrow resonances are possible in regular arrays of NPs, while Markel has elaborated the theory [13]. Several experimental verifications have also been provided [14][15][16][17][18][19][20][21][22][23], and considering the very narrow linewidth achievable (few nanometers), results hold promises for many applications in lasing, sensing, and metamaterials [24]. An interesting possibility is to study the coupling between diffractive and plasmon modes in the condition λ RA < λ LSP .…”
Section: Introductionmentioning
confidence: 99%
“…Schatz et al [11,12] have first suggested that these narrow resonances are possible in regular arrays of NPs, while Markel has elaborated the theory [13]. Several experimental verifications have also been provided [14][15][16][17][18][19][20][21][22][23], and considering the very narrow linewidth achievable (few nanometers), results hold promises for many applications in lasing, sensing, and metamaterials [24]. An interesting possibility is to study the coupling between diffractive and plasmon modes in the condition λ RA < λ LSP .…”
Section: Introductionmentioning
confidence: 99%
“…The beam spot on the sample was reduced to a diameter of 30 µm by inserting a pinhole aperture between the light source and the condenser, thereby giving a beam divergence of less than 1 deg. The arrays were then index matched with oil (n = 1.515) [31,32] and the transmitted light collected with an oil immersion lens (NA of 1.25). A long-pass filter (cutoff 500 nm) was inserted in the optical path after the collection objective to remove higher diffracted orders.…”
Section: Characterizationmentioning
confidence: 99%
“…As the radius of SPA decreases to 65 nm, the central wavelength of CR has a blue shift to 874 nm. Furthermore, when the central wavelength of CR approaches geometric resonant wavelength, the coupling effects lead to a significant narrowing of the reflection lineshape which has been studied both theoretically and experimentally [27,28]. Geometric resonant wavelength can be calculated by λ G =n·P, indicated by red dash line in Fig.…”
Section: Formation Of Fano Resonance In Bspamentioning
confidence: 98%